2009
DOI: 10.1111/j.1755-3768.2009.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between chronic glycosylated haemoglobin (HbA1c) level and macular volume in diabetes patients without macular oedema

Abstract: Acta Ophthalmol. 2010: 88: 753–758 Abstract. Purpose:  This study aimed to examine the correlation between glycosylated haemoglobin (HbA1c) level and macular volume in diabetes patients without diabetic macular oedema (DMO). Methods:  We carried out an observational, cross‐sectional study. Patients who had diabetes mellitus (DM) of ≥ 10 years duration without DMO were included. Only one eye of each patient was selected for analysis. Eyes with proliferative diabetic retinopathy were excluded. Central subfield t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
3
20
2
3
Order By: Relevance
“…Moon, at al [20] suggested that a high baseline HbA1c and a large reduction in HbA1c were risk factors for increase in macular thickness. Yeung, et al [21], showed that HbA1c level positively correlated with macular thickness in patients with type1 and 2 diabetes of10 or more years’ duration without diabetic macular edema. Chou, Moreira at al [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moon, at al [20] suggested that a high baseline HbA1c and a large reduction in HbA1c were risk factors for increase in macular thickness. Yeung, et al [21], showed that HbA1c level positively correlated with macular thickness in patients with type1 and 2 diabetes of10 or more years’ duration without diabetic macular edema. Chou, Moreira at al [22].…”
Section: Discussionmentioning
confidence: 99%
“…Yeung, http://at al. [21]–[23] concluded that meticulous diabetes control may slow the progression of early diabetic retinopathy and may play an important role in preventing macular dysfunction. In type 1 and 2 diabetes patients, strict follow-up of plasma glucose level could reduce the progression and development of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…42 In our study, the duration of diabetes and HbA1 C levels did not significantly affect macular thickness measurements. In contrast, previous studies have reported increased macular thickness with higher HbA1 C levels, 43,44 whereas a longer duration of diabetes was associated with thinner macula measurements in the absence of macula oedema. 45,46 However, these studies were not population-based, hence were susceptible to selection bias.…”
Section: Discussioncontrasting
confidence: 42%
“…Alterations in glucose metabolism lead to changes in the capillary walls of retinal vessels. This leads to breakdown of blood retinal barrier causing haemorrhages and seepage of exudates, which in turn present as detectable retinal thickening in OCT. [13][14][15] In contrast to our study, few researchers [16][17][18][19] reported early macular thickening in diabetic eyes, however, the difference was not statistically significant. In certain patients they observed significantly higher macular thickness in diabetics without clinical retinopathy when compared with controls.…”
Section: Discussioncontrasting
confidence: 82%